2013
DOI: 10.1007/s00345-013-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

Expanding utilization of robotic partial nephrectomy for clinical T1b and complex T1a renal masses

Abstract: In the hands of experienced surgeons, RAPN is a safe and reproducible approach for the treatment of cT1b and more challenging renal tumors, and could represent the way to expand the indications for minimally invasive conservative approach to RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…It has been suggested that RAPN may replace open PN as the standard of care for small renal masses 26 or at the very least alter the patient population that is offered a minimally invasive option for PN may expand. 3,14 Should this occur, it is important to ensure that all patients have equal access to the standard of care treatment modality, regardless of the primary paying modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that RAPN may replace open PN as the standard of care for small renal masses 26 or at the very least alter the patient population that is offered a minimally invasive option for PN may expand. 3,14 Should this occur, it is important to ensure that all patients have equal access to the standard of care treatment modality, regardless of the primary paying modality.…”
Section: Discussionmentioning
confidence: 99%
“…3,13 Understanding the role of hospital volume on RAPN outcomes is important in light of the significant increase in PN over the past decade and recommendations in favor of PN for the management of small renal masses. 3,14 We hypothesized that the hospital volume of RAPN would play a significant role in developing postoperative complications due to the complexity of PN. Perhaps, not surprisingly, nearly half of RAPNs in the United States are performed at the top 10% of hospitals by volume and being a high-volume RAPN hospital is independently associated with decreased risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that laparoscopic partial nephrectomy and robotic partial nephrectomy result in less blood loss and shorter recovery with similar long-term renal function and oncologic outcomes. 1,3,4,5,8 Patients with multiple complex renal masses often have bilateral disease, and the previous standard of radical nephrectomy would leave these patients on renal replacement therapy. 4 …”
Section: Discussionmentioning
confidence: 99%
“…SE), appear to be unrelated to margins status, according to the largest currently available evidence. 7,[14][15][16][17][18] We aimed to evaluate the predictors of PSM after NSS for RCC in one of the largest available prospective multi-institutional studies.…”
Section: Introductionmentioning
confidence: 99%